Pipelined production of high-strength fire-resistant magnesium oxide composite explosion-proof plate and preparation method thereof
Patent Information
- Application Number
- CN202511519968.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]为了克服现有的氧化镁水泥基防爆板抗爆性能不足的问题,本发明提出一种流水线生产高强耐火氧化镁复合防爆板及制备方法
1.通过面浆层、玄武岩网格布、中料层、玄武岩网格布和底浆层的五层复合结构设计形成梯度抗冲击体系,中料层钢纤维与木质纤维协同增韧,面浆层与底浆层的高强浆料抵抗表面应力,使板材整体抗弯强度提升40%以上,在爆炸冲击波作用下有效抑制脆性断裂。
Smart Images

Figure CN122956797A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite explosion-proof plate preparation technology, and in particular to a method for producing high-strength fire-resistant magnesium oxide composite explosion-proof plates on an assembly line. Background Technology
[0002] In the field of industrial explosion protection, magnesium oxide cement-based composite materials are used to manufacture protective panels due to their fire resistance. Existing technologies mainly improve the basic properties by adjusting the ratio of magnesium oxide to magnesium chloride, and supplement them with fiber reinforcement layers or metal mesh structures to enhance impact resistance. Common production processes employ layered casting or sandwich structure designs, and the curing process mostly relies on natural curing or a constant temperature and humidity environment.
[0003] Existing explosion-proof panels are heavy and expensive. Furthermore, the single-layer homogeneous structure or simple sandwich design of existing magnesium oxide cement-based explosion-proof panels leads to insufficient impact resistance, making them prone to brittle fracture under explosive loads. In addition, other fiber-reinforced materials have insufficient high-temperature resistance. Existing production processes mostly rely on intermittent workshop operations, with long curing cycles and large quality fluctuations, making it difficult to meet the stringent requirements for consistent panel performance in large-scale projects.
[0004] Therefore, in response to the problems mentioned above, this invention proposes a production line method for high-strength fire-resistant magnesium oxide composite explosion-proof panels and a preparation method thereof. By optimizing the material formula and the reinforcement layer layout design, and combining automated production line production with a stepped temperature-controlled curing process, the overall performance of the explosion-proof panels is improved. Summary of the Invention
[0005] To overcome the problem of insufficient explosion-proof performance of existing magnesium oxide cement-based explosion-proof boards, this invention proposes a production line method for high-strength fire-resistant magnesium oxide composite explosion-proof boards and its preparation method.
[0006] The technical solution of this invention is: a production line for high-strength fire-resistant magnesium oxide composite explosion-proof plates, comprising: Surface layer: a slurry layer with a thickness of 3–5 mm; First reinforcing layer: basalt fiber mesh fabric laid on the surface; Core layer: a medium-thickness layer of material, 20–25 mm thick; Second reinforcing layer: basalt fiber mesh fabric laid on the core layer; Base layer: A base slurry layer with a thickness of 3–5 mm; The top and bottom layers are made of the same material, while the core layer has an independent formulation.
[0007] Preferably, the composition of the topcoat and bottomcoat layers, by weight, includes: 100–110 parts magnesium oxide, 4–6 parts silica fume, 18–22 parts fly ash, 1–3 parts quartz sand, 0.1–0.15 parts PP fiber, 1.5–1.8 parts phosphoric acid, and 0.7–0.9 parts silane waterproofing agent.
[0008] Preferably, the core layer comprises, by weight, 100–110 parts magnesium oxide, 1.5–2.5 parts steel fiber, 30–40 parts wood fiber, 4–6 parts silica fume, 18–22 parts fly ash, 1.5–1.8 parts phosphoric acid, and 0.7–0.9 parts silane waterproofing agent.
[0009] Preferably, the basalt fiber mesh is a basalt fiber mesh with a mesh size of 5×5mm and a unit area mass of 160±10g / ㎡, and the first reinforcing layer and the second reinforcing layer are symmetrically laid.
[0010] As a preferred embodiment, a method for preparing high-strength fire-resistant magnesium oxide composite explosion-proof panels for automated production includes the following steps: S1, firstly, the raw materials are transported to the production line; S2, weigh the raw materials for the surface slurry layer, core layer and bottom slurry layer according to the design ratio; S3, mix the raw materials of the top slurry layer and the bottom slurry layer with magnesium chloride solution and stir until a uniform slurry is formed; mix the raw materials of the core layer with magnesium chloride solution and stir until a thick material with uniform fiber dispersion is formed; S4, in the mold, the bottom slurry layer is poured, the second reinforcing layer is laid, the core layer is laid, the first reinforcing layer is laid and the surface slurry layer is poured in sequence; S5 should be cured at a temperature of 40–60℃ and a humidity of 70–85% until it hardens. S6, demold the cured material; S7, the demolded material is cured in a natural environment; S8, cuts the material into standard-sized boards; S9 packages the standard sheet metal into the warehouse and then ships it.
[0011] Preferably, in step S2, the amount of magnesium chloride solution added during the mixing of the top slurry layer and the bottom slurry layer is 65–75% of the weight of magnesium oxide.
[0012] Preferably, in step S2, the amount of magnesium chloride solution added during core layer stirring is 60–70% of the weight of magnesium oxide.
[0013] Preferably, step S3 is completed using an automated paving line, with the paving speed controlled at 0.8–1.2 m / min and the vibration compaction frequency at 40–60 Hz.
[0014] Preferably, a gradient heating program is used during step S4 curing, which is adjusted according to the required board material model.
[0015] Preferably, the curing time in step S5 is set to 12–24 hours, and the curing time in step S7 is set to 7–14 days.
[0016] The beneficial effects of this invention are: 1. A gradient impact-resistant system is formed by a five-layer composite structure design consisting of a surface slurry layer, a basalt mesh cloth, a middle layer, a basalt mesh cloth, and a bottom slurry layer. The middle layer is reinforced by steel fibers and wood fibers, while the high-strength slurry in the surface slurry layer and the bottom slurry layer resists surface stress, thereby increasing the overall bending strength of the board by more than 40% and effectively suppressing brittle fracture under the action of explosive shock waves.
[0017] 2. The present invention has strong explosion resistance and impact resistance, with a compressive strength of over 50 MPa and an elastic modulus of up to 200 GPa, and can withstand an explosive shock wave of 0.5 MPa.
[0018] 3. This invention uses magnesium oxide as a cementing material and basalt fiber and steel fiber as reinforcing materials, making it suitable for fire and explosion protection facilities in the chemical industry. Basalt fiber enhances its high-temperature resistance and corrosion resistance, while steel fiber enhances its toughness and explosion resistance. The combination of the two significantly optimizes the overall performance of this invention. This invention can maintain its structural integrity for more than 2 hours at 1450℃, and its density is only one-fifth that of steel plates. At the same time, due to its strong acid and alkali resistance, it is suitable for various harsh chemical environments. Furthermore, this invention has strong plastic deformation capacity and can absorb explosive energy in the event of an explosion, thereby preventing brittle fracture.
[0019] 4. This invention is based on automated production line production, thereby realizing continuous material laying and gradient temperature-controlled curing, which greatly improves production efficiency. Attached Figure Description
[0020] Figure 1 The diagram shown illustrates the preparation process of this invention. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] This invention provides an embodiment: a method for producing high-strength fire-resistant magnesium oxide composite explosion-proof panels on an assembly line, comprising: Surface layer: a slurry layer with a thickness of 3–5 mm; First reinforcing layer: basalt fiber mesh fabric laid on the surface; Core layer: a medium-thickness layer of material, 20–25 mm thick; Second reinforcing layer: basalt fiber mesh fabric laid on the core layer; Base layer: A base slurry layer with a thickness of 3–5 mm; The top and bottom layers are made of the same material, while the core layer has an independent formulation.
[0023] The composition of the topcoat and bottomcoat layers, by weight, includes: 100–110 parts magnesium oxide, 4–6 parts silica fume, 18–22 parts fly ash, 1–3 parts quartz sand, 0.1–0.15 parts PP fiber, 1.5–1.8 parts phosphoric acid, and 0.7–0.9 parts silane waterproofing agent.
[0024] The core layer comprises, by weight, 100–110 parts magnesium oxide, 1.5–2.5 parts steel fiber, 30–40 parts wood fiber, 4–6 parts silica fume, 18–22 parts fly ash, 1.5–1.8 parts phosphoric acid, and 0.7–0.9 parts silane waterproofing agent.
[0025] The steel fiber is copper-plated. Ordinary steel fibers are easily corroded and rusted, which can cause volume expansion and damage to the matrix structure. The copper plating layer acts as a physical barrier to prevent chloride ions from directly contacting the steel fibers, thereby increasing the durability of the board in humid environments by more than 5 times.
[0026] Please see Figure 1 Furthermore, the preparation process of the present invention will be described as follows: S1, firstly, the raw materials are transported to the production line; S2, weigh the raw materials for the surface slurry layer, core layer and bottom slurry layer according to the design ratio; S3, mix the raw materials of the top slurry layer and the bottom slurry layer with magnesium chloride solution and stir until a uniform slurry is formed; mix the raw materials of the core layer with magnesium chloride solution and stir until a thick material with uniform fiber dispersion is formed; S4, in the mold, the bottom slurry layer is poured, the second reinforcing layer is laid, the core layer is laid, the first reinforcing layer is laid and the surface slurry layer is poured in sequence; S5 should be cured at a temperature of 40–60℃ and a humidity of 70–85% until it hardens. S6, demold the cured material; S7, the demolded material is cured in a natural environment; S8, cuts the material into standard-sized boards; S9 packages the standard sheet metal into the warehouse and then ships it.
[0027] Furthermore, this invention provides an embodiment for the production of high-strength fire-resistant magnesium oxide composite explosion-proof panels measuring 3000×1200×30mm on an assembly line: Weigh the following components according to the formula ratio: 105 kg magnesium oxide, 70 kg magnesium chloride solution, 2 kg steel fiber, 6 m² basalt fiber mesh (5×5 mm mesh size, 160 g / m²), 35 kg wood fiber, 0.12 kg PP fiber, 2 kg quartz sand, 5 kg silica fume, 20 kg fly ash, 1.6 kg phosphoric acid, and 0.8 kg silane waterproofing agent. Pre-treat all materials at a constant temperature (25±2℃) for 24 hours to ensure stable moisture content.
[0028] Add magnesium oxide, silica fume, fly ash, quartz sand, PP fiber, phosphoric acid, and silane waterproofing agent to a high-speed mixer and dry mix for 3 minutes until uniform. Then slowly add magnesium chloride solution and continue mixing for 5 minutes until a smooth slurry is formed. Let it stand for 10 minutes to defoam before use.
[0029] Magnesium oxide, steel fiber, wood fiber, silica fume, fly ash, phosphoric acid, and silane waterproofing agent are added to a forced mixer and dry-mixed for 5 minutes to ensure uniform fiber dispersion. Then, magnesium chloride solution is added and the mixture is stirred at low speed for 8 minutes to form a fiber-reinforced thick material, thus ensuring that there is no fiber clumping.
[0030] A release agent is sprayed onto the automatic conveying mold. First, a 4mm thick base slurry layer is poured. Then, a layer of basalt fiber mesh is laid and compacted with a roller press. Next, a 22mm thick core layer is laid. The vibrating table is vibrated at a frequency of 50Hz for 30 seconds. Then, a second layer of basalt fiber mesh is laid. Finally, a 4mm thick surface slurry layer is poured. The whole structure is vibrated for 10 seconds to eliminate air bubbles, thus forming a five-layer composite structure.
[0031] The molded boards are placed in a constant temperature curing room. The temperature is raised to 40°C for the first 2 hours, maintained for 2 hours, and then raised to 55°C. The boards are then cured at a constant temperature for 18 hours to ensure that the compressive strength of the boards reaches more than 80% of the initial strength.
[0032] After demolding, the boards are stacked in a natural environment with a temperature of 20-30℃ and a humidity of 60-70%, with wooden strips between them to ensure ventilation. They are cured for 14 days until they are completely solidified, and water is sprayed once a day to keep them moist.
[0033] The edges are trimmed to a standard size of 3000mm×1200mm using a CNC cutting machine. The density (1.75g / cm³), bending strength (18MPa), fire resistance limit (120min), and impact resistance (10kJ / ㎡ without cracking) of the board are tested. After passing the test, the board is put into storage.
[0034] After testing, the bending strength was found to be 18.2 MPa, the interlaminar peel strength was 2.8 MPa, the fire resistance limit was 120 min (1100℃), and the strength retention rate after 50 freeze-thaw cycles was 96.5%.
[0035] Furthermore, the present invention provides an embodiment for the production of water-resistant magnesium oxide composite explosion-proof panels measuring 3000×1200×30mm on an assembly line: Weigh the following components according to the formula ratio: 105 kg magnesium oxide, 70 kg magnesium chloride solution, 2 kg steel fiber, 6 m² basalt fiber mesh (5×5 mm mesh size, 160 g / m²), 35 kg wood fiber, 0.12 kg PP fiber, 2 kg quartz sand, 5 kg silica fume, 20 kg fly ash, 1.2 kg phosphoric acid, and 1.2 kg silane waterproofing agent. Pre-treat all materials at a constant temperature (25±2℃) for 24 hours to ensure stable moisture content.
[0036] Add magnesium oxide, silica fume, fly ash, quartz sand, PP fiber, phosphoric acid, and silane waterproofing agent to a high-speed mixer and dry mix for 3 minutes until uniform. Then slowly add magnesium chloride solution and continue mixing for 6 minutes until a fluid slurry is formed, thus ensuring that the silane waterproofing agent is fully dispersed. Let stand for 10 minutes to defoam before use.
[0037] Magnesium oxide, steel fiber, wood fiber, silica fume, fly ash, phosphoric acid, and silane waterproofing agent are added to a forced mixer and dry-mixed for 5 minutes to ensure uniform fiber dispersion. Then, magnesium chloride solution is added and the mixture is stirred at low speed for 10 minutes to form a fiber-reinforced thick material, thus ensuring that there is no fiber clumping.
[0038] A release agent is sprayed onto the automatic conveying mold. First, a 4mm thick base slurry layer is poured. Then, a layer of basalt fiber mesh is laid and compacted with a roller press. Next, a 22mm thick core layer is laid. The vibrating table is vibrated at a frequency of 50Hz for 30 seconds. Then, a second layer of basalt fiber mesh is laid. Finally, a 4mm thick surface slurry layer is poured. The whole structure is vibrated for 10 seconds to eliminate air bubbles, thus forming a five-layer composite structure.
[0039] The molded sheet material is placed in a constant temperature curing room. The temperature is raised to 40°C for the first 2 hours, maintained for 4 hours, then raised to 50°C. After 12 hours of constant temperature curing, the temperature is raised to 60°C and maintained for 2 hours.
[0040] After demolding, the boards are stacked in a natural environment with a temperature of 20-30℃ and a humidity of 60-70%, with wooden strips between them to ensure ventilation. They are cured for 14 days until they are completely solidified, and water is sprayed once a day to keep them moist.
[0041] The edges are trimmed to a standard size of 3000mm×1200mm using a CNC cutting machine. The density (1.75g / cm³), bending strength (18MPa), fire resistance limit (120min), and impact resistance (10kJ / ㎡ without cracking) of the board are tested. After passing the test, the board is put into storage.
[0042] After testing, the water absorption rate of the finished board was reduced to 1.8%, and the strength retention rate was 98% after 50 freeze-thaw cycles.
[0043] Furthermore, the present invention provides an embodiment for the production of thin explosion-proof panels measuring 3000×1200×25mm on an assembly line: Weigh the following components according to the formula ratio: 87.5 kg magnesium oxide, 58.3 kg magnesium chloride solution, 1.67 kg steel fiber, 5 m² basalt mesh cloth, 29.2 kg wood fiber, 0.1 kg PP fiber, 1.67 kg quartz sand, 4.17 kg silica fume, 16.7 kg fly ash, 1.33 kg phosphoric acid, and 0.67 kg silane waterproofing agent. Pre-treat all materials at a constant temperature (25±2℃) for 24 hours to ensure stable moisture content.
[0044] Add magnesium oxide, silica fume, fly ash, quartz sand, PP fiber, phosphoric acid, and silane waterproofing agent to a high-speed mixer and dry mix for 3 minutes until uniform. Then slowly add magnesium chloride solution and continue mixing for 4 minutes until a smooth slurry is formed. Let it stand for 10 minutes to defoam before use.
[0045] Magnesium oxide, steel fiber, wood fiber, silica fume, fly ash, phosphoric acid, and silane waterproofing agent are added to a forced mixer and dry-mixed for 4 minutes to ensure uniform fiber dispersion and avoid the problem of reduced reinforcement effect due to reduced thickness. Then, magnesium chloride solution is added and stirred at low speed for 8 minutes to form fiber-reinforced thick material, thereby ensuring that there is no fiber clumping.
[0046] A release agent is sprayed onto the automatic conveying mold. First, a 3mm thick base slurry layer is poured. Then, a layer of basalt fiber mesh is laid and compacted with a roller press. Next, a 19mm thick core layer is laid. The vibrating table is vibrated at a frequency of 55Hz for 20 seconds. Then, a second layer of basalt fiber mesh is laid. Finally, a 3mm thick surface slurry layer is poured. The whole structure is vibrated for 10 seconds to eliminate air bubbles, thus forming a five-layer composite structure.
[0047] The molded sheet material is placed in a constant temperature curing room at 40℃ for 1 hour, and then the temperature is raised to 50℃ for 8 hours.
[0048] After demolding, the boards are stacked in a natural environment with a temperature of 20-30℃ and a humidity of 60-70%, with wooden strips between them to ensure ventilation. They are cured for 14 days until they are completely solidified, and water is sprayed once a day to keep them moist.
[0049] The edges are trimmed to a standard size of 3000mm×1200mm using a CNC cutting machine. The density (1.75g / cm³), bending strength (18MPa), fire resistance limit (120min), and impact resistance (10kJ / ㎡ without cracking) of the board are tested. After passing the test, the board is put into storage.
[0050] After testing, the density of the finished board was reduced to 1.65 g / cm³, the fire resistance limit was still 1.5h (tested according to standard GB / T9978), and the bending strength was ≥15MPa, making it suitable for lightweight explosion-proof partition walls.
[0051] Furthermore, the present invention provides an embodiment for the production of ultra-thick explosion-proof plates of 3000×1200×40mm on an assembly line: Weigh the following components according to the formula ratio: 140 kg magnesium oxide, 93.3 kg magnesium chloride solution, 2.67 kg steel fiber, 9 m² basalt mesh cloth, 46.7 kg wood fiber, 0.16 kg PP fiber, 2.67 kg quartz sand, 6.67 kg silica fume, 26.7 kg fly ash, 2.13 kg phosphoric acid, and 1.07 kg silane waterproofing agent. Pre-treat all materials at a constant temperature (25±2℃) for 24 hours to ensure stable moisture content.
[0052] Add magnesium oxide, silica fume, fly ash, quartz sand, PP fiber, phosphoric acid, and silane waterproofing agent to a high-speed mixer and dry mix for 3 minutes until uniform. Then slowly add magnesium chloride solution and continue mixing for 5 minutes until a smooth slurry is formed. Let it stand for 10 minutes to defoam before use.
[0053] Magnesium oxide, steel fiber, wood fiber, silica fume, fly ash, phosphoric acid, and silane waterproofing agent are added to a forced mixer and dry-mixed for 5 minutes to ensure uniform fiber dispersion. Then, magnesium chloride solution is added and the mixture is stirred at low speed for 10 minutes to form a fiber-reinforced thickener, thereby ensuring that the steel fiber is evenly distributed in the thickener.
[0054] A release agent is sprayed onto the automatic conveying mold. First, a 5mm thick base slurry layer is poured. Then, a layer of basalt fiber mesh is laid and compacted with a roller press. Next, a 30mm thick core layer is laid. The vibrating table is vibrated at a frequency of 50Hz for 30 seconds. Then, a second layer of basalt fiber mesh is laid. Finally, a 5mm thick surface slurry layer is poured. The whole structure is vibrated for 10 seconds to eliminate air bubbles, thus forming a five-layer composite structure.
[0055] The molded sheet material is placed in a constant temperature and curing chamber. The temperature is raised to 35°C for the first 2 hours, maintained for 3 hours, then raised to 45°C and cured at a constant temperature for 5 hours. Then the temperature is raised to 60°C and cured at a constant temperature for 12 hours, with the total curing time extended to 20 hours.
[0056] After demolding, the boards are stacked in a natural environment with a temperature of 20-30℃ and a humidity of 60-70%, with wooden strips between them to ensure ventilation. They are cured for 21 days until they are completely solidified, and water is sprayed once a day to keep them moist.
[0057] The edges are trimmed to a standard size of 3000mm×1200mm using a CNC cutting machine. The density (1.75g / cm³), bending strength (18MPa), fire resistance limit (120min), and impact resistance (10kJ / ㎡ without cracking) of the board are tested. After passing the test, the board is put into storage.
[0058] After testing, the compressive strength of the plate was found to be ≥35MPa, and it can withstand an explosion impact of 1.2MPa, making it suitable for core components of explosion-proof walls in chemical plants.
[0059] Through the above steps, the present invention is composed of a five-layer composite structure consisting of a surface slurry layer, a basalt mesh fabric, a middle layer, a basalt mesh fabric, and a bottom slurry layer. The high-strength slurry in the surface slurry layer and the bottom slurry layer resists surface stress, while the steel fiber and wood fiber in the middle layer work together to toughen the material, thereby significantly improving the overall bending strength of the board. This effectively suppresses brittle fracture under the action of an explosive shock wave, thus solving the problem of insufficient explosion-proof performance of existing magnesium oxide cement-based explosion-proof boards.
[0060] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments that can be applied to other fields. However, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A production line for high-strength fire-resistant magnesium oxide composite explosion-proof panels, characterized in that, Including: Surface layer: a slurry layer with a thickness of 3–5 mm; First reinforcing layer: basalt fiber mesh fabric laid on the surface; Core layer: a medium-thickness layer of material, 20–25 mm thick; Second reinforcing layer: basalt fiber mesh fabric laid on the core layer; Base layer: A base slurry layer with a thickness of 3–5 mm; The top and bottom layers are made of the same material, while the core layer has an independent formulation.
2. The high-strength fire-resistant magnesium oxide composite explosion-proof plate produced on an assembly line according to claim 1, characterized in that, The composition of the topcoat and bottomcoat layers, by weight, includes: 100–110 parts magnesium oxide, 4–6 parts silica fume, 18–22 parts fly ash, 1–3 parts quartz sand, 0.1–0.15 parts PP fiber, 1.5–1.8 parts phosphoric acid, and 0.7–0.9 parts silane waterproofing agent.
3. The high-strength fire-resistant magnesium oxide composite explosion-proof plate produced on an assembly line according to claim 1, characterized in that, The core layer comprises, by weight, 100–110 parts magnesium oxide, 1.5–2.5 parts steel fiber, 30–40 parts wood fiber, 4–6 parts silica fume, 18–22 parts fly ash, 1.5–1.8 parts phosphoric acid, and 0.7–0.9 parts silane waterproofing agent.
4. The high-strength fire-resistant magnesium oxide composite explosion-proof plate produced on an assembly line according to claim 1, characterized in that: The basalt fiber mesh is a basalt fiber mesh with a mesh size of 5×5mm and a unit area mass of 160±10g / ㎡, and the first reinforcing layer and the second reinforcing layer are laid symmetrically.
5. A method for preparing high-strength refractory magnesium oxide composite explosion-proof panels for automated production, using the automated production method for high-strength refractory magnesium oxide composite explosion-proof panels as described in claims 1-4, characterized in that, It includes the following steps: S1, firstly, the raw materials are transported to the production line; S2, weigh the raw materials for the surface slurry layer, core layer and bottom slurry layer according to the design ratio; S3, mix the raw materials of the top slurry layer and the bottom slurry layer with magnesium chloride solution and stir until a uniform slurry is formed; mix the raw materials of the core layer with magnesium chloride solution and stir until a thick material with uniform fiber dispersion is formed; S4, in the mold, the bottom slurry layer is poured, the second reinforcing layer is laid, the core layer is laid, the first reinforcing layer is laid and the surface slurry layer is poured in sequence; S5 should be cured at a temperature of 40–60℃ and a humidity of 70–85% until it hardens. S6, demold the cured material; S7, the demolded material is cured in a natural environment; S8, cuts the material into standard-sized boards; S9 packages the standard sheet metal into the warehouse and then ships it.
6. The method for preparing high-strength fire-resistant magnesium oxide composite explosion-proof plates for automated production line manufacturing according to claim 5, characterized in that: In step S2, the amount of magnesium chloride solution added during the mixing of the top and bottom slurry layers is 65–75% of the weight of magnesium oxide.
7. The method for preparing high-strength fire-resistant magnesium oxide composite explosion-proof plates for automated production according to claim 5, characterized in that: In step S2, the amount of magnesium chloride solution added during core layer stirring is 60–70% of the weight of magnesium oxide.
8. The method for preparing high-strength fire-resistant magnesium oxide composite explosion-proof plates for automated production according to claim 5, characterized in that: Step S3 is completed using an automated paving line, with the paving speed controlled at 0.8–1.2 m / min and the vibration compaction frequency at 40–60 Hz.
9. The method for preparing high-strength fire-resistant magnesium oxide composite explosion-proof plates for automated production line manufacturing according to claim 5, characterized in that: Step S4, during curing, employs a gradient heating program, which is adjusted according to the required board material model.
10. The method for preparing high-strength fire-resistant magnesium oxide composite explosion-proof plates for automated production according to claim 5, characterized in that: The curing time for step S5 is set to 12–24 hours, and the curing time for step S7 is set to 7–14 days.